58.1k views
1 vote
What is the solution to the system of equation? 2x+6y=-6 4x-3y=-12

2 Answers

2 votes

Answer:

2x+6y=-6 ........1

4x-3y=-12 ........2

Simplify equation 1

2x + 6y = -6

Divide both sides by 2

You will get

x + 3y = -3

Make x the subject

x = - 3 - 3y

Substitute x into equation 2

4x - 3y = - 12

4(- 3 - 3y) - 3y = - 12

-12 + 12y - 3y = -12

9y = -12 + 12

9y = 0

Divide both sides by 9

y = 0

Substitute y = 0 into x = - 3 - 3y

You will get

x = - 3 - 3(0)

x = -3

Therefore x = - 3 and y = 0

Hope this helps

User You Qi
by
5.4k points
3 votes

Answer:

(-3, 0)

Explanation:

We can solve this algebraically (substitution or elimination) or graphically.

Step 1: Multiply the first equation by -2

-4x - 12y = 12

4x - 3y = -12

Step 2: Add the 2 equations together and solve for y

-15y = 0

y = 0

Step 3: Plug y back into an original equation to get x

2x + 6(0) = -6

2x = -6

x = -3

And we have your answer!

User Rodolphe LAMPE
by
5.0k points